2021
DOI: 10.1101/2021.07.01.450671
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prefrontal stimulation prior to motor sequence learning alters multivoxel patterns in the striatum and the hippocampus

Abstract: Motor sequence learning (MSL) is supported by dynamical interactions between hippocampal and striatal networks that are thought to be orchestrated by the prefrontal cortex. In the present study, we tested whether individually-tailored theta-burst stimulation of the dorsolateral prefrontal cortex (DLPFC) prior to MSL, can modulate multivoxel response patterns in the stimulated cortical area, the hippocampus and the striatum. Response patterns were assessed with multivoxel correlation structure analyses of funct… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 77 publications
0
8
1
Order By: Relevance
“…In contrast to our previous work showing a differential effect of iTBS vs. cTBS on task-related brain patterns and functional connectivity (Gann et al, 2021b(Gann et al, , 2021a, the present analyses did not show such stimulation-specific effects. It is worth noting though that -similar to the present results -our previous studies did not highlight any effect of stimulation condition on brain activity during initial training (Gann et al, 2021a).…”
Section: Stimulation-induced Effects Did Not Differ Between Active St...contrasting
confidence: 99%
See 4 more Smart Citations
“…In contrast to our previous work showing a differential effect of iTBS vs. cTBS on task-related brain patterns and functional connectivity (Gann et al, 2021b(Gann et al, , 2021a, the present analyses did not show such stimulation-specific effects. It is worth noting though that -similar to the present results -our previous studies did not highlight any effect of stimulation condition on brain activity during initial training (Gann et al, 2021a).…”
Section: Stimulation-induced Effects Did Not Differ Between Active St...contrasting
confidence: 99%
“…Importantly, it remains uncertain whether altering these neural signatures with experimental interventions can effectively influence consolidation. In line with a series of hippocampal-targeted non-invasive brain stimulation studies in the declarative memory domain (e.g., (Wang et al, 2014; Kim et al, 2018; Tambini et al, 2018; Freedberg et al, 2019; Hermiller et al, 2019, 2020; Warren et al, 2019)), we recently showed that learning-related responses in the hippocampus were influenced by stimulation of the dorsolateral prefrontal cortex (DLPFC) applied prior to initial MSL (Gann et al, 2021b, 2021a). Specifically, inhibitory - as compared to facilitatory - thetaburst stimulation (TBS) of the DLPFC altered functional connectivity patterns in fronto-hippocampal networks over the course of learning.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations